Analisis Yuridis Pertimbangan Hakim dalam Menjatuhkan Putusan terhadap Warga Negara Asing yang Menyalahgunakan Izin Tinggal Kunjungan untuk Bekerja di Indonesia - Afif Desy Rahmadea; Yusuf Eko Nahuddin; Andi Purwanto; Raditya Feda Rifandhana (Bhirawa Law Journal, 2023)
The background of this research is that foreign citizens of Australian nationality have violated Article 122 letter a of the Republic of Indonesia Law No. 6 of 2011 concerning Immigration. The defendant deliberately carried out the activity of renting out his villa called Sunset Sala villa which is located in Sudaji Village, Sawan District, Buleleng Regency for medical meditation activities so that it is not in accordance with the intent and purpose of granting a residence permit granted to the defendant on a visit visa to Indonesia, as a tourist. not for business or business activities. This study uses a descriptive-juridical-normative research method. The results of this study are the Decision of the Singaraja District Court in case Number 127/Pid.Sus/2018/PN.Sgr. in the description of the judge's considerations in imposing a sentence in accordance with 122 letter a of the Republic of Indonesia Law No. 6 of 2011 concerning Immigration by imposing administrative sanctions and setting aside pro justicia sanctions which will take longer.